EMOTIONS AFFECTING MENTAL HEALTH IN ADOLESCENCE - R, Gadha T.; K, Krishnaja Mol (International Journal of Psychosocial Rehabilitation, 2020)
Mental Health and Mental Illness are the two relatable concepts in Health Sciences. Subjects which usually deal with health or something related to health care are included in health sciences. This category of sciences usually deals with three branches such as Physical Health, Mental Health and Social Health. As adolescents are taken into consideration, usually there are various reasons for their mental illness which could be due to varying physical, social, or emotional changes. Such changes include poverty, violence, addiction, abuse etc. are some of the prominent factors that made adolescents more vulnerable and rebellious. For the growth and maintaining emotional and social habits which are very important for mental well-being in the crucial time period in the life of youths. The mental health problems which appear in the life of young children especially are mostly not recognized and are hence difficult to treat as it became severe. As per the saying “A healthy mind lives in a healthy body”, it’s almost true and is in a way mentioned. In this paper, various emotions leading to the mental illness of youths, suicide attempts because of mental stress, some preventive measure, some ways to recognize the problems, etc. were being illustrated.